Resurgence of multidrug-resistant tuberculosis during the COVID-19 pandemic in Korea - Kim, Tae Hoon; Heo, I Re; Kim, Ho Cheol (Kosin Medical Journal (Online), 2025)
Background: The coronavirus disease 2019 pandemic, which emerged in 2020, disrupted healthcare systems globally, affecting tuberculosis (TB) diagnosis and reporting. This study assessed the impact of the pandemic on the incidence of TB, multidrug-resistant TB (MDR-TB), and TB-related deaths in Korea between 2016 and 2023.Methods: Data from annual reports from 2016 to 2023 were used to analyze the incidence of TB and MDR-TB, as well as TB-related deaths. Trends before and after the pandemic were compared to assess the pandemic’s impact on TB management. Key variables included age and sex-based TB incidence, MDR-TB incidence, and number of TB-related deaths.Results: From 2016 to 2023, the total number of TB cases declined from 39,245 to 19,540, while new TB cases dropped from 30,892 to 15,640, representing reductions of 50.2% and 49.4%, respectively. The most pronounced decline occurred between 2020 and 2023. Individuals ≥65 years of age consistently had the highest TB burden, although the number of cases decreased by 28.6%. MDR-TB cases declined to 399 in 2020 but subsequently rose to 551 in 2023. TB-related deaths decreased from 2,186 in 2016 to 1,322 in 2022, with most deaths occurring in individuals ≥65 years of age.Conclusions: While the incidence of TB and TB-related deaths decreased during the study period, MDR-TB exhibited an upward trend after 2020. Continued monitoring is needed to understand whether these changes were driven by pandemic-related disruptions or healthcare improvements.